2015
DOI: 10.1001/jamaoto.2015.1467
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience of a Patient Navigation Model for Head and Neck Cancer

Abstract: The goal of treatment recommendations for HNC within 2 weeks was shown to be reasonable and attainable. Further research should address the delays encountered by patients with psychosocial barriers and those with synchronous lung nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…25,26 Other potential solutions might include increased centralization of care at large health systems to avoid delays related to care transitions and patient navigation programs with a focus on vulnerable populations for whom lack of social support, poor health literacy, or limited access to transportation are likely important barriers to timely treatment. 27,28 We found a significant interaction of DTS and HPV status. In patients with HPV-negative tumors, a DTS ≥ 11 days (the optimal predictive threshold for patients with HPV-negative tumors) led to a more than 1.5-fold increase in the risk of mortality; however, rising DTS had no significant effect on survival in HPV-positive tumors.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…25,26 Other potential solutions might include increased centralization of care at large health systems to avoid delays related to care transitions and patient navigation programs with a focus on vulnerable populations for whom lack of social support, poor health literacy, or limited access to transportation are likely important barriers to timely treatment. 27,28 We found a significant interaction of DTS and HPV status. In patients with HPV-negative tumors, a DTS ≥ 11 days (the optimal predictive threshold for patients with HPV-negative tumors) led to a more than 1.5-fold increase in the risk of mortality; however, rising DTS had no significant effect on survival in HPV-positive tumors.…”
Section: Discussionmentioning
confidence: 64%
“…With this program, they demonstrated a reduction in time from referral to final diagnosis of 24 days to 7‐10 days and showed that more than 95% of surgically treated patients underwent operation within 28 days of the initial presenting visit . Other potential solutions might include increased centralization of care at large health systems to avoid delays related to care transitions and patient navigation programs with a focus on vulnerable populations for whom lack of social support, poor health literacy, or limited access to transportation are likely important barriers to timely treatment …”
Section: Discussionmentioning
confidence: 99%
“…4144 However, there is a dearth of data about the association of patient navigation with timely initiation of treatment for patients with HNC. 45,46 Whether patient navigation can decrease delays initiating treatment for HNC is a question that merits further research.…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian Authority enacted a law in 2012 which specifies a maximum period of 60 days from diagnosis to treatment for cancer patients [6]. In the United States, a patient navigation model for head and neck cancer patients has been proposed to decrease the interval period between presentation to a clinic and treatment [25]. Since April 2013, Taiwan’s Ministry of Health and Welfare has subsidized hospitals which have implemented ‘‘MDT management for cancer patients” in order to improve the quality of cancer diagnosis and management [10].…”
Section: Discussionmentioning
confidence: 99%